1999
DOI: 10.1017/s0950268899002083
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and geographical distributions of reported cases of Escherichia coli O157[ratio ]H7 infection in Ontario

Abstract: The distribution of 3001 cases of verocytotoxigenic Escherichia coli (VTEC) reported in the Province of Ontario, Canada, were examined to describe the magnitude of this condition geographically and to evaluate the spatial relationship between livestock density and human VTEC incidence using a Geographical Information System. Incidence of VTEC cases had a marked seasonal pattern with peaks in July. Areas with a relatively high incidence of VTEC cases were situated predominantly in areas of mixed agriculture. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
101
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 16 publications
14
101
0
Order By: Relevance
“…Michel et al [29] have previously observed a significantly higher incidence of VTEC O157 infection in rural areas of Ontario, while Innocent et al [30] have reported a decreasing cumulative incidence in concurrence with increasing population density in Scotland. Likewise, previous studies by Strachan et al [16] and Pearl et al [31] provide evidence of the influence of geographical location on VTEC infection incidence, with reported VTEC incidence rates 1·7-4 times greater in rural areas than in urban areas.…”
Section: Discussionmentioning
confidence: 98%
“…Michel et al [29] have previously observed a significantly higher incidence of VTEC O157 infection in rural areas of Ontario, while Innocent et al [30] have reported a decreasing cumulative incidence in concurrence with increasing population density in Scotland. Likewise, previous studies by Strachan et al [16] and Pearl et al [31] provide evidence of the influence of geographical location on VTEC infection incidence, with reported VTEC incidence rates 1·7-4 times greater in rural areas than in urban areas.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work also has shown that generic E. coli (18), E. coli O157:H7 (27), Salmonella (28), and Listeria (29,30) are positively associated with livestock density or proximity to livestock. Similarly, studies that have aggregated reported EHEC illnesses to county or district levels have generally observed higher EHEC infection rates in counties with higher cattle densities, although this approach infers rather than directly links cases and exposures (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, our work indicates that achieving food safety and nature conservation goals in produce-growing landscapes is possible. contaminated waterways, to aggregate reported illnesses to a county or district level, and to correlate infection rates with land use patterns (19,20).…”
mentioning
confidence: 99%
“…Rural residents were at an increased risk for VTEC infection. That finding may also explain the relatively high incidence of VTEC infections in Prince Edward Island, where the cattle density (0.17 per hectare) approaches that of the regions of Ontario with the highest incidence of VTEC infection (0.2 cattle per hectare; Michel et al 1999). Factors which may be associated with the increased risk include recurrent exposure to cattle, surface water and shallow well contamination with cattle manure used as fertilizer and consumption of locally processed foods .…”
Section: Geographic Distributionmentioning
confidence: 97%
“…In Canada, reports of E. coli O157:H7 infection have been more frequent in the western provinces than in the east (Griffin and Tauxe 1991;Nataro and Kaper 1998). Michel et al (1999) investigated the relative risks of VTEC infection associated with living in rural vs. urban environments by examining the geographic distribution of VTEC infections in Ontario, Canada, between 1990 and 1995. Reported annual rates of VTEC infection were consistently higher in rural areas (5.4 per 100 000) as compared to urban areas (4.4 per 100 000).…”
Section: Geographic Distributionmentioning
confidence: 99%